The Effect of Managerial Workload and Welfare Level on the Performance of School Principals in North Penajam Paser Regency - Munasih, Munasih; Amalia, Kaniati; Hazin, Mufarrihul; Khamidi, Amrozi (Journal of English Language and Education, 2026)
The performance of school principals plays a crucial role in determining the effectiveness of school management and the overall quality of education. Principals are required to carry out various managerial responsibilities while also maintaining professional performance under different organizational conditions. However, the increasing managerial workload and the level of welfare received by principals are often considered factors that may influence their performance in managing schools effectively. This study aims to empirically analyze the influence of managerial workload and welfare level on the performance of public and private elementary school principals in North Penajam Paser Regency, both partially and simultaneously. The study used a quantitative approach with an ex post facto causal design. The study population consisted of 109 principals, and all were sampled through a saturated sampling technique. Data collection was conducted using a five-level Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was carried out through descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that managerial workload had a positive and significant effect on principal performance with a significance value of 0.001 and a beta coefficient of 0.212. The welfare level also had a positive and significant effect with a significance value of 0.000 and a beta coefficient of 0.739 and was the most dominant variable. Simultaneously, both variables contributed 83.6% to the variation in principal performance. These findings indicate that improving principal performance requires strengthening managerial capacity as well as implementing policies that continuously enhance the welfare of school principals.